1998
DOI: 10.1159/000022419
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Thrombin Generation after Coronary Thrombolysis with rt-PA or Streptokinase with Simultaneous Heparin versus Heparin Alone

Abstract: This study compares the extent of inhibition of thrombin generation and activity achieved in patients with acute myocardial infarction receiving fibrinolytic treatment (streptokinase SK, or rt-PA) and concomitant intravenous heparin treatment adjusted to the patients’ weight with that achieved with the same heparin regimen but without fibrinolytic therapy. The study involved 90 patients, grouped according to their treatment: SK+heparin; rt-PA+heparin, and heparin without thrombolytic agents. Prothrombin fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…The CPU generation in the present dog model coincides with thrombus formation (when thrombin is generated) and an increase in thrombin generation after coronary thrombolysis with t-PA (22). The link between thrombin generation and proCPU activation is further strengthened by the observation that inhibition of thrombin by melagatran attenuates CPU generation (Figure 3).…”
Section: Discussionsupporting
confidence: 70%
“…The CPU generation in the present dog model coincides with thrombus formation (when thrombin is generated) and an increase in thrombin generation after coronary thrombolysis with t-PA (22). The link between thrombin generation and proCPU activation is further strengthened by the observation that inhibition of thrombin by melagatran attenuates CPU generation (Figure 3).…”
Section: Discussionsupporting
confidence: 70%
“…The residual thrombin in clot has been called postclotting thrombin (bound thrombin). After percutaneous transluminal coronary angioplasty, levels of fibrinopeptide A, thrombin-antithrombin III complex and prothrombin fragments 1+2 were significantly increased in many patients, indicating coronary thrombosis by procoagulant activity [6, 7]. It was reported that the coronary thrombosis by procoagulant activity was resistant to the treatment by high doses of heparin [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…(15) In addition, reocclusion and restenosis of blood vessels usually occurs after PTCR (16,17) and the cause of the restenosis could be correlated to the activity of the generated thrombin (postclotting thrombin) from fibrin clot and fibrin thrombin. (18)(19)(20) We therefore attempted to produce a MAb against thrombin to measure the thrombin concentration and postclotting thrombin concentration. A discussion took place regarding which of the MAbs against thrombin could recognize the structure of thrombin.…”
Section: Introductionmentioning
confidence: 99%